2011
DOI: 10.1515/jpm.2011.071
|View full text |Cite
|
Sign up to set email alerts
|

Maternal preeclampsia is associated with an increased risk of retinopathy of prematurity

Abstract: Maternal preeclampsia was found to be associated with increased ROP development risk in premature infants. ROP was also more severe in infants born to pre-eclamptic mothers. The role of maternal preeclampsia in the occurrence and severity of ROP remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 25 publications
2
41
1
6
Order By: Relevance
“…Although we and other authors 14,27,28 found a detrimental role played by hypertension on ROP, others showed a protective one. [29][30][31] A possible explanation for these discordant results lies in the data analysis.…”
Section: Figurecontrasting
confidence: 65%
See 2 more Smart Citations
“…Although we and other authors 14,27,28 found a detrimental role played by hypertension on ROP, others showed a protective one. [29][30][31] A possible explanation for these discordant results lies in the data analysis.…”
Section: Figurecontrasting
confidence: 65%
“…If being SGA is both caused by hypertension/preeclampsia and associated with ROP, then adjusting for birth weight in studies analyzing the role of hypertensive disorders could give rise to a problem of "overadjustment." In fact, studies that investigate the role played by hypertension on ROP and correct-for-birth weight in their analysis find that hypertension is protective, [28][29][30] whereas others that do not adjust (eg, this study and refs 14,27,28) find the opposite.…”
Section: Figurementioning
confidence: 70%
See 1 more Smart Citation
“…The category of HDP was consistent among studies. Ten studies reported preeclampsia [5,10,13–18,20–21], two reported gestational hypertension [16,20], and two reported HDP [89]. Outcomes were categorized as 2 broad categories: “any stage ROP” and “severe ROP”.…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide hypertensive Disorder of Pregnancy (HDP) affects around 10% of all pregnancies with pre-eclampsia and eclampsia together accounting for 10-15% of all direct maternal deaths 1 and major burden of perinatal morbidity and mortality [6][7][8][9] . There is worldwide regional variation in distribution of maternal deaths due to HDP with 16.1% occurring in developed countries, 9.1% in Africa, 9.1% in Asia, and around 25.7% in Latin America and the Caribbean 2 .…”
mentioning
confidence: 99%